(untitled) (Global Journals of Research in Engineering, 2023)
This paper presents a model to plan personnel safety on FPSO platform systems A Transshipment System model of utilities personnel worker safety status on FPSO Platform is derived from Bow Tie Risk system and pinch technique Data obtained from deepwater multinational oil and gas operator in Nigeria is used to simulate the safety index of personnel safety from 10 to 90 on the risk threat targeted The plots of risk reduction and safety composite graph for the risk target are presented for personnel on critical and non-critical assignments and safety targets for the process worker on FPSO simulated in MATLAB software environment to be T1 0 553733 T2 0 49836 T3 0 276867 T1 0 110747 and T2 0 055373 for safety targets of 100 90 50 20 and 10 consecutively